Respuestas

2013-03-30T19:52:52+01:00

3xcuadrado -1x + 1=0

 

a= 3 

B=-1

c=1

 

-(-1) raiz cuadrada (-1) al cuadrado -4 .3.1

              partido por 3.2

 

1masmenos /raizcuadrada de 12 

       partido por6                                     

                                                                                  

2013-03-30T20:21:07+01:00

3 x2 - 5 x + 2 x - 1 + 2 + x2

Se reunen terminos semejantes, quedando:

 

4 x2 - 3 x + 1, se descompone:

 

( 2 x - 1) ( 2 x - 1)

 

Suerte...!!!